The untapped potential of vaginal microbiome diagnostics for improving women’s health - Da Silva, Ana Sofia; Anwar, Saba; Park, Suenie; Park, Sunwha; Goodfellow, Laura; Sergaki, Chrysi (Frontiers in Cellular and Infection Microbiology, 2025)
Microbiome research has expanded rapidly over the past 15 years; however, the primary focus has been on the gut microbiome. Although understudied, the vaginal microbiome holds significant potential to improve women’s health. In this paper, we describe the current clinical diagnostic techniques utilised in women’s health and examine their drawbacks and limitations. We also discuss emerging diagnostic technologies based on microbiome analysis that could enable greater precision in diagnosis and personalised treatment. We additionally emphasise the need for standardisation in microbiome analysis and strengthening the knowledge base to enable advancements in accurate diagnosis, ultimately improving patient outcomes. This article aims to highlight opportunities in the field that can transform women’s health outcomes and outline the necessary actions to realise these opportunities, thereby enhancing women’s lives.